Risk Factors for Fever After Esophageal Endoscopic Submucosal Dissection and Its Derived Technique - Liao, Foqiang; Zhu, Zhenhua; Lai, Yongkang; Pan, Xiaolin; Long, Shunhua; Zhou, Xiaojiang; Li, Guohua; Zhu, Yin; Chen, Youxiang; Shu, Xu (Frontiers in Medicine, 2022)
Background Fever is one of the postoperative adverse events of endoscopic submucosal dissection and its derived technique, but the probability and risk factors of postoperative fever are still unclear. The aim of the current study was to investigate the incidence and risk factors of postoperative fever after esophageal lesion removal. Methods We conducted a retrospective study of 446 patients who underwent esophageal endoscopic submucosal dissection and its derived technique between January 2014 and January 2020. Cases included in this study were divided into fever and non-fever groups. Results Postoperative fever developed in 135 patients (30.3%). The median (range) highest fever temperature was 38 (37.8–38.4)°C, the median (range) duration of fever was 1 (1–2) day, and 127 (94.1%) patients developed fever within 24 h after operation. Through logistic regression analysis, factors associated with postoperative fever were age (OR: 1.740, 95% CI: 1.005–3.013, p = 0.048), lesion size (OR: 2.007, 95% CI: 1.198–3.362, p = 0.008), operation time (OR: 3.007, 95% CI: 1.756–5.147, p < 0.001) and nasogastric tube placement (OR: 1.881, 95% CI: 1.165–3.037, p = 0.010), while prophylactic antibiotics (OR: 0.181, 95% CI: 0.082–0.401, p < 0.001) were negatively associated with fever. Conclusions Age ≥52 years old, lesion size ≥19 mm, operation time ≥37 min, and nasogastric tube placement are risk factors for postoperative fever after esophageal endoscopic submucosal dissection and its derived technique, prophylactic antibiotic use after operation may help reduce fever rate. Attention should be paid to such patients to minimize the risk of postoperative fever.